Hostile, Benevolent, Implicit: How Different Shades of Sexism Impact Gendered Policy Attitudes - Gothreau, Claire; Arceneaux, Kevin; Friesen, Amanda (Frontiers in Political Science, 2022)
Advances in gender equality and progressive policies are often stymied by cultural sexist systems and individual-level sexist attitudes. These attitudes are pervasive but vary in type – from benevolent to hostile and implicit to explicit. Understanding the types of sexism and their foundations are important for identifying connections to specific social and political attitudes and behaviors. The current study examines the impact of various manifestations of sexism on attitudes regarding policies and public opinion issues that involve gender equality or have gendered implications. More specifically, we look at attitudes on reproductive rights, support for the #MeToo Movement, equal pay, and paid leave policies. In Study 1 we use data from a high-quality web panel (n=1,400) to look at the relationship between hostile, benevolent, and implicit sexism, and reproductive rights attitudes, as well as support for the #MeToo Movement. In Study 2 we use data from the American National Election Study (n=4,270) to examine the relationship between hostile and modern sexism and attitudes on abortion, equal pay, and paid family leave. Overall, these results reveal a complicated relationship between different conceptualizations of sexism and gendered attitudes, underscoring the need to consider how different forms of sexism shape broader social and political views, from both a normative perspective for societal change and a measurement approach for research precision.